Audience Interpretation of the Film “Kamisama Wa Bali Ni Iru” Concerning Religiosity, Gender, and Economic Codes - Sutanto, Marisa Rianti; Kosasih, Marcella Melly (Bina Nusantara University, 2024)
The research aimed to interpret the film “Kamisama wa Bali ni Iru” according to the audience’s perception of whether the Bali expressed in the film reflects Balinese ethnic identity. “Kamisama wa Bali ni Iru” is a film by a Japanese director released in 2015 in the comedy-drama genre. The film was set almost entirely in Bali, which was the space where the events took place. Through a review of the narrative of “Kamisama wa Bali ni Iru” on the diegetic aspect, three things were dominantly reflected in the events of the film in the Balinese space, namely religiosity, gender, and the economy of society. By referring to the audience reception method, the audience who acted as the giver of meaning to the film text were nine young adults of Balinese ethnicity. Audience interpretation was understood through interviews, with questions set through the codes that appeared in the film’s scenes, namely the codes of religiosity, gender, and the economy of society. The interviews with the nine viewers were a reproduction of meaning into a new text, and the results of the viewers’ answers were categorized according to three positions: dominant, negotiated, and oppositional. The results show that the film tends to cause misperceptions of Balinese ethnic identity according to the codes of religiosity and economy. However, the audience affirms the gender code in this film as a representation of Balinese society. The novelty of the research is that it proves that the movie “Kamisama wa Bali ni Iru” can be a medium to introduce Bali, although it needs to be supported by explanations to avoid misperceptions regarding codes of religiosity and economy.